Scrotal Flap for Finger Reconstruction - S Mishra (Indian Journal of Plastic Surgery)
Finger injuries with exposed bone, tendon or joint may need skin cover by a distant flap. Scrotal flap has been successfully used as a pedicled distant flap in four patients with finger injuries. This is a preliminary report on alternative use of scrotal skin.